Supramolecular detection of geometrical differences of azobenzene carboxylates. Issue 16 (20th April 2016) - Ulatowski, Filip; Dąbrowa, Kajetan; Jurczak, Janusz
Graphical abstract: Highlights: Dynamic combinatorial library (DCL) is sensitive to the geometry of the template. Photoisomers of the template induce different compositions of the library. Composition of the library can be modified by light stimulus. Abstract: In dynamic combinatorial chemistry, the geometry of a template can be translated into the composition of a library of interchanging components. In this study, such a dynamic combinatorial library was used for the first time to detect and evaluate differences in the geometry of isomers of photoswitchable azobenzene based templates.